The Relevance of Ecclesiastical Law in Facing Justice Issues in Indonesia: Justice in Abraham Kuyper's Perspective - Eunike, Pratiwi; George, Annie (Indonesian Journal of Religious, 2025)
This study explores the role of the church in addressing social justice in Indonesia through the application of ecclesiastical law. Despite Indonesia being based on Pancasila, social inequality remains a significant challenge. The aim of this research is to explore how ecclesiastical law can contribute to resolving social justice issues by incorporating Abraham Kuyper's thoughts on the sovereignty of God. The research employs a qualitative method, including a literature review and theological analysis. It analyzes Kuyper's works, such as Lectures on Calvinism and Our Program, which emphasize that God's sovereignty encompasses all aspects of social, political, and economic life. Additionally, in-depth interviews with church leaders provide practical perspectives on the challenges and opportunities in fulfilling the church's social role. The findings show that the church can make a meaningful contribution to addressing social injustice by integrating Kuyper's views and applying ecclesiastical law. The church holds moral authority in advocating for social justice, even while operating within a secular legal system. This study contributes by demonstrating that the church can have a real impact through fair public policy advocacy and social services based on theological values, with a collaborative strategy focused on concrete actions to create a more just social order.